Prebiotic Driven Increases in IL-17A Do Not Prevent Campylobacter jejuni Colonization of Chickens - Flaujac Lafontaine, Geraldine M.; Richards, Philip J.; Connerton, Phillippa L.; O’Kane, Peter M.; Ghaffar, Nacheervan M.; Cummings, Nicola J.; Fish, Neville M.; Connerton, Ian F. (Frontiers in Microbiology, 2020)
Worldwide Campylobacter jejuni is a leading cause of foodborne disease. Contamination of chicken meat with digesta from C. jejuni-positive birds during slaughter and processing is a key route of transmission to humans through the food chain. Colonization of chickens with C. jejuni elicits host innate immune responses that may be modulated by dietary additives to provide a reduction in the number of campylobacters colonizing the gastrointestinal tract and thereby reduce the likelihood of human exposure to an infectious dose. Here we report the effects of prebiotic galacto-oligosaccharide (GOS) on broiler chickens colonized with C. jejuni when challenged at either an early stage in development at six days of age or twenty days old when campylobacters are frequently detected in commercial flocks. GOS-fed birds had increased growth performance, but the levels of C. jejuni colonizing the cecal pouches were unchanged irrespective of the age of challenge. Dietary GOS modulated the immune response to C. jejuni colonization by increasing cytokine IL-17A expression whilst reducing IL-17F. Correspondingly, reduced diversity of the cecal microbiota was associated with Campylobacter colonization in GOS-fed birds. In birds challenged at six days-old the reduction in microbial diversity was accompanied by an increase in the relative abundance of Escherichia spp. Whilst immuno-modulation of the Th17 pro-inflammatory response did not prevent C. jejuni colonization of the intestinal tract of broiler chickens, the study highlights the potential for combinations of prebiotics and specific competitors (synbiotics) to engage with the host innate immunity to reduce pathogen burdens.